2004
DOI: 10.1037/1076-8998.9.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Customer-Related Social Stressors and Burnout.

Abstract: Although almost all literature on burnout implicitly assumes that burnout is primarily caused by stressful employee-customer interactions, only a few studies have addressed this empirically. A principal-components analysis of a newly developed instrument assessing various forms of customer-related social stressors (CSS) in 3 different service jobs (N = 591) revealed 4 themes of CSS: disproportionate customer expectations, customer verbal aggression, disliked customers, and ambiguous customer expectations. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
655
1
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(707 citation statements)
references
References 94 publications
(153 reference statements)
27
655
1
24
Order By: Relevance
“…Frontline staff selection, support and training are essential, if not critical, as substantial evidence points to consumers' dissatisfaction with their complaint-handling experiences (Tax, Brown and Chandrashekaran 1998). Furthermore, managers who do not deal with emotional stresses facing their frontline employees will be likely to encounter rising staff absenteeism, lack of commitment, burnout, stress and turnover among employees (Dorman and Zapf 2004). These issues, in turn, can lead to lower consumer satisfaction, lower re-patronage and potentially higher levels of negative word of mouth, all eventually having a negative impact on service quality and profitability (Zeithaml 2002).…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontline staff selection, support and training are essential, if not critical, as substantial evidence points to consumers' dissatisfaction with their complaint-handling experiences (Tax, Brown and Chandrashekaran 1998). Furthermore, managers who do not deal with emotional stresses facing their frontline employees will be likely to encounter rising staff absenteeism, lack of commitment, burnout, stress and turnover among employees (Dorman and Zapf 2004). These issues, in turn, can lead to lower consumer satisfaction, lower re-patronage and potentially higher levels of negative word of mouth, all eventually having a negative impact on service quality and profitability (Zeithaml 2002).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…For example, recent work by Hennig-Thurau et al (2006) and Pugh (2001) has demonstrated the impact of service providers' positive displays on consumers. In related organizational research, studies have investigated the postinteraction implications of consumers' negative emotion on service providers, such as stress (Dorman and Zapf 2004), and absenteeism (Grandey, Dickter and Sin 2004).…”
mentioning
confidence: 99%
“…In the organizational context, threat stressors would include varying forms of workplace aggression and victimization, which thwart employees' psychological needs for belonging, trust in others, self-worth, and influence over the environment (see Aquino & Thau, 2009). In this family are stressors such as workplace bullying and harassment (e.g., Einarsen & Raknes, 1997), customer-related social stressors (Dormann & Zapf, 2004), and abusive supervision (e.g., Tepper, 2000), among others. High levels of job insecurity and other forms of precarious work arguably also represent a threat stressor, with high potential for personal harm or loss (e.g., Elst, Van den Broeck, De Witte, & De Cuyper, 2012;Waenerlund, Virtanen, & Hammarstrom, 2011).…”
Section: Distinguishing Hindrances From Threatsmentioning
confidence: 99%
“…There is a growing body of empirical data suggesting that also non-traumatic general life stress as, for example, daily, occupational stressors (e.g. Dormann & Zapf, 2004;Story & Repetti, 2006), worrying about one's fi nancial situation and health (Grulke et al, 2006), time pressure (Roxburgh, 2004) and life transitions stressors (e.g. adjustment to college, residential independence; Kiselica, Baker, Thomas, & Reedy, 1994;Lee & Gramotnev, 2007) has negative effects on subjective and physiological wellbeing.…”
Section: Introductionmentioning
confidence: 99%